Tracer Study Alumni: Upaya Peningkatan Layanan Pembelajaran Program Studi Pendidikan Agama Islam UHAMKA - Lismawati Lismawati; Shobah Shofariyani Iryanti (Universitas Muhammadiyah Prof Dr Hamka, 2020)
The research objectives of the PAI UHAMKA tracer study are to analyze the personal data of graduates, the views of graduates regarding the education services provided, the level of user satisfaction related to the professional competence of graduates, and the implementation of Al Islam and Muhammadiyah values